CLOZAPINE INDUCED EXTRAPYRAMIDAL SYMPTOMS FOLLOWING ALCOHOL CONSUMPTION IN PATIENT WITH SCHIZOPHRENIA AND ALCOHOL DEPENDENCE SYNDROME: A CASE REPORT OF SIALORRHEA, ACUTE AKATHISIA AND DYSTONIA - AKHIL ARUN (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Clozapine (CLZ), a second-generation or atypical antipsychotic, although not recommended as the first-line drug of choice in the treatment of schizophrenia and schizoaffective disorders; however, it is recommended in the treatment of Treatment-Resistant Schizophrenia and in schizophrenic patients to decrease the recurrent risk of suicidal behavior. For the cytochrome P450 isoenzymes CYP1A2, CYP2D6, and CYP3A4, CLZ serves as a substrate. CLZ also exhibits drug-food interaction with alcohol leading to an increase in the risk of seizures and extrapyramidal symptoms. A case of a 36-year-old male patient with a known history of paranoid schizophrenia and alcohol dependence syndrome came with complaints of dystonia and hypersalivation 1 day following the consumption of alcohol after ingestion of tablet CLZ. After clinical pharmacist intervention, the doses were titrated and the patient improved gradually. With this, it can be postulated that the concomitant use of alcohol with CLZ can be a predisposing factor for drug toxicity in the patients and hence patients should be monitored and counseled to abstain from the use of alcohol while on CLZ therapy.